Organização dos trabalhadores do Sistema Único de Assistência Social no contexto das terceirizações, privatizações e precarização do trabalho - Rossin, Elizabeth Conceição (2015)
This dissertation intends to put under review the forms of organization of the Social Assistance Single System workers from Campinas/SP, in a context where productive restructuring, privatization policy, and the State employment system reorganization have played a role in the maintenance and survival of the capital, inflicting penury and misery to the working class. Connected to the stories of our time and the past, as a social product, and historically experienced by men, we ve traveled through the path of resistances and struggles needed to confront the material and objective conditions that make the daily life of these workers precarious. They ve experienced job and income fluctuation, flexibility in labor rights, temporary employment contracts of individuals or independent legal entities, subcontracting, outsourcing, lack of labor social protection, all contributing to the destruction of conquests and rights historically forged by the working class. Based on dialectical materialist Marxist method, this research values the dialogues with authors and works with conceptual basis grounded on the articulation of critical knowledge of the studied object, using the conception that reality will explain the ideas and not the opposite. The representation spaces of workers interests from the Social Assistance Single System have been immersed in a heatproof environment to class struggle and haven t even advocated immediate interests and claims, if they go against the ruling power. We use semi structured interviews with unions and opposition groups, as well as the formation of a focal group with workers in order to discuss the most important questions that the issue raises among municipal public servants in Campinas and those employed privately by the Social Assistance Single System. These data unveil their importance in the research investigative path, not only from a quantitative point of view, but in the sense that the individuals involved are products of a historical time